Super-multiplexed imaging and coding in the range of radio frequency - Yuhang Jiang; Yifan Fan; Limin Chen; Hongyu Lin; Jinhao Gao (Nature Communications)
Abstract The era of the Internet has led to an information explosion, creating significant challenges for current techniques in information storage and access. High-performance strategies that expand existing methods offer a promising solution. Imaging-based approaches are vital for information perception but remain underexplored for information processing due to limited multiplexity. Here, we introduce 19F magnetic resonance imaging-Empowered information Assess and Storage Technique (FEAST), enabled by 22 fluorinated quaternary ammonium derivatives with distinct 19F chemical shifts. We developed three coding platforms for FEAST: fluorinated choline analog solutions, fluorinated deep eutectic solvents, and fluorinated ionogels. These platforms allow 2-spatial-dimensional applications, such as 16-bit encoding, “dual-color” watermarking, multiplexed Colorcodes, and encrypted QR codes, as well as 3-spatial-dimensional applications like “cubic” information storage, implanted anti-counterfeit labels, and FEAST-guided encryption. This work highlights FEAST’s potential for advanced information storage and access, which is inspiring for further developments with versatile and robust coding platforms.